Pengaruh Promo Event 6.6 Flash Sale Terhadap Perilaku Konsumtif Mahasiswa - Pakpahan, Roida; Febriyanti, Shinta; Berliana, Diva; Esmeralda, Rizqi Nur (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
E-Commerce is the favorite shopping place that is most used by today's people, one of which is students, online shopping is increasingly popular because the shopping process can be done anytime and anywhere. Students are e-Commerce consumers who are vulnerable to consumptive behavior. Event Sale Promos that offer big discounts and other interesting promotions can make students more impulsive in making purchases. The aim of the research is to analyze the influence of the 6.6 flash sale event promo on student consumptive behavior using the purposive sampling method. The research results show that there is a significant influence on changes in the level of student consumptive behavior during the 6.6 flash sale promo event. The ability to control oneself when shopping online is really needed, especially during the 6.6 flash sale promo event, so as not to get caught up in impulsive buying consumer behavior which can be detrimental to students' psychological well-being.